Instilling an Attitude of Tolerance Through Citizenship Courses for Students at Sunan Kalijaga State Islamic University, Yogyakarta - Indah Lestari Hasibuan; Nur Hidayat (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Indonesia, which is rich in diversity, especially in terms of culture, requires its people, especially us as Indonesian citizens, to instill a mindset of tolerance for one another. This is very important to foster harmony, comfort, and well-being between individuals, especially in the context of this research which focuses on university students. Tolerance involves mutual respect and appreciation between individuals and groups, where as humans, we must be aware of the ethics and politeness embedded in each of us. The purpose of this study is to determine the attitudes and tolerance of students of the Akidah and Islamic Philosophy study program towards citizenship issues, especially those related to multiculturalism. The research methodology used is qualitative, using a naturalistic approach. Data collection used interview excerpts and field notes conducted at the State Islamic University Sunan Kalijaga Yogyakarta. By using these data collection techniques, researchers conducted research at the Faculty of Ushuluddin and Islamic Thought to collect the necessary research data.